An Unusual Presentation of Malignant Melanoma (Nepal Medical College Journal, 2021)
Melanoma is one of the aggressive malignancy arising from the melanocyte. Melanoma usually occurs in the mucus membrane and choroid. There are few cases who may present with lymph node, breast and other involvement. However, few may have an atypical origin and rarely the origin may be unknown. Its aggressive presentation, diagnosis and prognosis sometimes is very challenging to the physician. The mainstay of the diagnosis remains the histopathology and immuno-histochemistry (IHC). Varieties of treatment have evolved from surgical excision to systemic chemotherapy and immunotherapy with promising result, the treatment is still challenging. A 30 years old lady presented with lump in her both breasts and generalized lymphadenopathy. Excisional biopsy revealed Diffuse large B cell Non Hodgkin lymphoma (NHL) but IHC was in favour of melanoma. The final diagnosis was cutaneous melanoma of trunk with atypical presentation (generalized lymphadenoapthy and bilateral breast metastasis).